2015
DOI: 10.1111/mec.13248
|View full text |Cite
|
Sign up to set email alerts
|

Sky island diversification meets the multispecies coalescent – divergence in the spruce‐fir moss spider (Microhexura montivaga, Araneae, Mygalomorphae) on the highest peaks of southern Appalachia

Abstract: Microhexura montivaga is a miniature tarantula-like spider endemic to the highest peaks of the southern Appalachian mountains and is known only from six allopatric, highly disjunct montane populations. Because of severe declines in spruce-fir forest in the late 20th century, M. montivaga was formally listed as a US federally endangered species in 1995. Using DNA sequence data from one mitochondrial and seven nuclear genes, patterns of multigenic genetic divergence were assessed for six montane populations. Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 93 publications
(254 reference statements)
1
68
0
Order By: Relevance
“…Cryptic diversity is an essential component of diagnosing biodiversity, and it is difficult to detect, especially under ongoing global climate change and habitat loss (Balint et al., ; Bickford et al., ). Empirical studies have identified evolutionary patterns of cryptic diversity similar to our study in other biodiversity hotspots (Bell et al., ; Carnaval, Hickerson, Haddad, Rodrigues, & Moritz, ; Demos, Peterhans, Agwanda, & Hickerson, ; Hedin, Carlson, & Coyle, ; Muñoz‐Ortiz, Velásquez‐Álvarez, Guarnizo, & Crawford, ; Wachter et al., ). However, previous studies did not consider the role of niche conservatism in impacting cryptic speciation.…”
Section: Discussionsupporting
confidence: 84%
“…Cryptic diversity is an essential component of diagnosing biodiversity, and it is difficult to detect, especially under ongoing global climate change and habitat loss (Balint et al., ; Bickford et al., ). Empirical studies have identified evolutionary patterns of cryptic diversity similar to our study in other biodiversity hotspots (Bell et al., ; Carnaval, Hickerson, Haddad, Rodrigues, & Moritz, ; Demos, Peterhans, Agwanda, & Hickerson, ; Hedin, Carlson, & Coyle, ; Muñoz‐Ortiz, Velásquez‐Álvarez, Guarnizo, & Crawford, ; Wachter et al., ). However, previous studies did not consider the role of niche conservatism in impacting cryptic speciation.…”
Section: Discussionsupporting
confidence: 84%
“…This conclusion is based on a two-step analytical approach for identifying distinct lineages in a taxon that has been used in some recent species delimitation studies (that is, Leaché and Fujita, 2010;Satler et al, 2013;Hedin et al, 2015). The first step (discovery) involves assigning samples to putative lineages, and is followed by a second (validation) step in which the putative lineages are tested for phylogenetic distinctiveness.…”
Section: Identifying Significant Phylogenetic Lineagesmentioning
confidence: 99%
“…As shown by Hedin et al (2015), groups characterized by strong population structure present some of the most challenging systems for delimitation, especially when inferences are limited to genetic data. In such cases, methods for delineating formal groups (that is, species, conservation units) may 'over-split' major genetic groups, and factors such as sample size can play an important role in the inference of whether such groups are recognized or not (see Niemiller et al, 2012 for an empirical example).…”
Section: Identifying Significant Phylogenetic Lineagesmentioning
confidence: 99%
“…Further attention should be also directed at the geographically disjunct Palos Verdes population, which is genetically distinct from Sitalcina flava for multiple genes (Figures 3, 4). Finally, because we failed to find obvious morphological differences between disjunct populations of Sitalcina peacheyi and Sitalcina flava , and because multispecies coalescent models might oversplit genetically structured populations (Niemiller et al 2012, Hedin et al 2015), we do not further split Sitalcina peacheyi and Sitalcina flava at this time.…”
Section: Resultsmentioning
confidence: 99%
“…As such, incongruence in gene tree topologies should largely reflect incomplete lineage sorting, consistent with the assumptions of most multispecies coalescent methods (Fujita et al 2012). Conversely, extreme population genetic structuring across naturally fragmented habitats may represent a deviation from model assumptions (Niemiller et al 2012, Hedin et al 2015). …”
Section: Introductionmentioning
confidence: 99%